Hyperfine-interaction-driven Aharonov-Bohm effect in mesoscopic rings - Vagner, I. D.; Wyder, P.; Rozhavsky, A. S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
It is shown qualitatively that lifting of the electron spin degeneracy by a hyperfine field, which is generated by a nonequilibrium nuclear spin distribution, and breaking of the left-right symmetry by the spin-orbit interaction in a closed ring produces under certain conditions a persistent current, which demonstrates the Aharonov-Bohm-like oscillations with time in GaAs/AlGaAs-based mesoscopic rings even in the absence of an external magnetic field. The typical time interval of these (meso-nucleospinic) oscillations is of the order of several seconds, which is typical of the nuclear spin relaxation times in heterojunctions.